Forbidden Fruit Ancient Near Eastern Sexual Metaphors - Veenker, Ronald A. (2001)
In the literature of Sumer, Babylon and Assyria one encounters a broad variety of sexual metaphors. This study focuses upon sexual metaphors taken from garden imagery, including such terms as "fruit" and "eating," found in a variety of cuneiform texts. After cataloging a select few ancient Near Eastern examples of such metaphors, the focus shifts to ancient Hebrew literature, the Bible and the Talmud, seeking similar examples of fruit, garden and eating images. Following the presentation of several biblical and talmudic sexual metaphors, a detailed analysis of the Garden of Eden narrative in the Hebrew Scriptures reveals that the biblical writer was familiar with such usage and even employed sexual fruit metaphors it. the story of Adam and Eve. Finally, in pursuit of a better understanding of "knowledge" and "sexual knowing," a comparison is made between the Garden narrative and an episode from the Gilgamesh Epic known as the "Seduction of Enkidu" (tablet I:160-93). From this comparison we learn that the "ascent of knowledge" theme is a part of the structure of both narratives.